Dionisio da Silva: Um criptojudeu nas garras da Inquisição no Piauí colonial - MOURA FILHO, Ferdinand Almeida de (2018)
The present research aimsto understand, through a crime-process, the organization and working of the Inquisition in Brazil, particularly the Piauí region, in the first half of the eighteenth century. Dionísio da Silva`s case structures the research. He was the first Piauí`s resident that the Inquisition investigated and the first New-Christian of this specific region (and apparently the only one) to be taken to the Holy Office in Lisbon, where the process would happen. The research also intends to give voice to this character. Therefore, based on his trajectory, I will shed light on Crypto-Judaism elements rooted in the Brazilian colonial society, primarily in the Paraíba and Piauí regions in the first half of the eighteenth century.